Fabrication and dual imaging properties of quantum dot/silica core-shell particles immobilized with gold nanoparticles. (19th September 2018) - Li, Ting-ting; Inose, Tomoya; Oikawa, Takahiro; Tokunaga, Masayuki; Hatoyama, Keiichiro; Nakashima, Kouichi; Kamei, Takashi; Gonda, Kohsuke; Kobayashi, Yoshio
ABSTRACT: The present work proposes a preparation method for core-shell nanoparticles composed of quantum dots (QDs), SiO2, large Au nanoparticles (Au L ), and small Au nanoparticles (Au S ). The QDs were silica-coated with a sol-gel method using tetraethyl orthosilicate (QD/SiO2 ). Au L and Au S were fabricated by reducing Au 3+ ions with sodium citrate and tetrakis(hydroxymethyl)phosphonium chloride in water, respectively. Amino groups were introduced onto QD/SiO2 surface by using (3-aminopropyl)-triethoxysilane (QD/SiO2 /NH2 ). Both Au L and Au S were immobilized on QD/SiO2 /NH2 by successively reacting Au L and Au S with QD/SiO2 /NH2 (QD/SiO2 /NH2 /Au L /Au S ). Surface modification of QD/SiO2 /NH2 /Au L /Au S was performed by using polyethylene glycol (PEG) with a thiol group (QD/SiO2 /NH2 /Au L /Au S /PEG). The QD/SiO2 /NH2 /Au L /Au S /PEG colloid solution could be clearly imaged via its fluorescence. Its computed tomography (CT) value per unit concentration of Au (M) was 1.2 × 10 4 HU/M. The QD/SiO2 /NH2 /Au L /Au S /PEGs were circulated in a mouse through blood vessels, and some of them became trapped and accumulated in the liver and spleen. Graphical Abstract: